In the Vermicular: Review of Janelle A. Schwartz, Worm Work: Recasting Romanticism - Bayer, Ellen (Humanimalia, 2013)
Janelle A. Schwartz, Worm Work: Recasting Romanticism. Minneapolis: University of Minnesota Press, 2012. 304 pp. 82.50 hb; 27.50 pb.